Seoritae Extract Reduces Prostate Weight and Suppresses Prostate Cell Proliferation in a Rat Model of Benign Prostate Hyperplasia. (19th February 2014) - Jang, Hoon; Bae, Woong-Jin; Yuk, Seung-Mo; Han, Dong-Seok; Ha, U-Syn; Hwang, Seong-Yeon; Yoon, Shin-Hee; Kim, Sae-Woong; Han, Chang-Hee
Abstract : Seoritae is a type of black soybean that is known to have health-promoting effects due to its high isoflavone and anthocyanin contents. We evaluated whether Seoritae extract (SE) had beneficial effects on the reduction of prostate weight in a rat model of benign prostatic hyperplasia (BPH). BPH was induced by intramuscular injections of testosterone enanthate once a week for 5 weeks in Sprague-Dawley rats, and rats were treated with or without daily oral doses of SE during BPH induction. After 5 weeks, the oxidative stress (superoxide dismutase and 8-hydroxy-2-deoxyguanosine), apoptosis (caspase-3), and activity of 5-alpha reductase were evaluated in the serum and prostate. The SE treatment group showed a significant decrease in prostate weight, oxidative stress, apoptosis, and 5-alpha reductase activity compared to the nontreated BPH group. These results show that SE is effective in decreasing the weight and proliferation of the prostate, and suggest that SE may be an effective treatment for BPH.